2012
DOI: 10.4103/0973-8258.104930
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacopoeial and physicochemical properties of α-cellulose and microcrystalline cellulose powders derived from cornstalks

Abstract: Background: Suitable α-cellulose and microcrystalline cellulose powders for use in the pharmaceutical industry can be derived from agricultural wastes. Aims: The pharmacopoeial and physicochemical properties of cornstalk α-cellulose (CCC) and cornstalk microcrystalline cellulose powders (MCCC) were compared to a commercial brand of microcrystalline cellulose (Avicel PH101) to evaluate their usefulness as pharmaceutical excipients. Settings and Design: Physicochemical properties of an excipient play a very cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The results of the true density of SO-MCC as shown in Table 1 showed that the difference between SO-MCC and Avicel PH 102 were not significant. The higher values of true density for SO-MCC compared to the Avicel PH 102 suggests that the SO-MCC might exhibit better compressibility [22].…”
Section: Figure 1 Dsc Image Of So-mccmentioning
confidence: 96%
“…The results of the true density of SO-MCC as shown in Table 1 showed that the difference between SO-MCC and Avicel PH 102 were not significant. The higher values of true density for SO-MCC compared to the Avicel PH 102 suggests that the SO-MCC might exhibit better compressibility [22].…”
Section: Figure 1 Dsc Image Of So-mccmentioning
confidence: 96%
“…The porosity of MCC-GossL was the highest while that of MCC-GossF was the least. These high porosity characteristic would impair the free flow of these materials (Azubuike, Odulaja, Okhamafe, 2012). Considering the angle of repose (Table II) the powders were classified as excellent.…”
Section: Micromeritic Propertiesmentioning
confidence: 99%
“…Some commercial brands of MCC such as Avicel®, Emcocel®, Comprecel® and Microcel® may show variations in the degree of crysrallinity, moisture content, surface area, porous structure, and molecular weight. These physical differences possessed by each brand would affect the products functionality when used as an excipient (Azubuike, Odulaja, Okhamafe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Corn demand has been increased throughout the years to satisfy human consumption resulting in important lignocelluloses residues which could be utilized as raw material to manufacture particleboard and papers They are cheap, ready available, renewable lignocellulosic source, biodegradable from nature, excellent source of cellulose, hemicellulose and lignin and good fibers structure in terms of length and diameter (Azubuike et al 2012). It is reported that hemicellulose content is higher and the lignin content lower in straw and stalks materials (Rowell et al 2000.…”
Section: Introductionmentioning
confidence: 99%